Odpowiedź :
[tex]a) (-\frac{1}{2})^{3} *(-\frac{1}{2})^{4} *2^{7} =-(\frac{1}{2})^{3} *(\frac{1}{2})^{4} *2^{7}=-2^{-3} *2^{-4} * 2^{7} =-1[/tex]
[tex]b) 0,1^{8} * 0,2^{8} : 0,02^{6} =(\frac{1}{10})^{8} *(\frac{1}{5})^{8}:(\frac{1}{50})^{6}=\frac{1}{10^{8} } * \frac{1}{5^{8} } : \frac{1}{50^{6} }= \frac{1}{10^{8} } * \frac{1}{5^{8} } * 50^{6} = \frac{1}{10^{8} } * \frac{1}{5^{8} }* 5^{6} *10^{6} = \frac{1}{10^{2} }* \frac{1}{5^{2} }=\frac{1}{100} * \frac{1}{25} =\frac{1}{2500}[/tex]
[tex]c) 0,5^{6} * (-0,5)^{7} : 0,05^{13} = -(\frac{1}{2})^{6}* (\frac{1}{2})^{7} : (\frac{1}{20})^{13} =-\frac{1}{64} * \frac{1}{128} : \frac{1}{20^{13} } = -\frac{1}{64} * \frac{1}{128} *20^{13} =-\frac{20^{13} }{8192}[/tex]
[tex]d) \frac{44^{4} }{22^{3} } = \frac{2^{4}*22^{4} }{22^{3} } =2^{4} * 22= 16*22=352[/tex]
[tex]e) \frac{64^{2}*36^{2} }{6^{3}*2^{7} } =\frac{2^{12}*6^{4} }{6^{3}*2^{7} }=2^{5} *6=32*6=192[/tex]
[tex]f) \frac{4^{6}*8^{6} }{32^{5} } = \frac{2^{12}*2^{18} }{2^{25} } =\frac{2^{18} }{2^{13} }=2^{5} =32[/tex]